2016
DOI: 10.3892/ol.2016.4528
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis in patients with thymoma affects survival rate following extended thymectomy

Abstract: Abstract. Thymomas are the most common adult tumors in the anterior mediastinal compartment, and a significant amount of thymomas are complicated by myasthenia gravis (MG). Extended thymectomy (ET) is the primary treatment method for thymomas and is used to completely resect possible ectopic thymus to avoid recurrence. Studies on the effect of MG in thymoma patients following ET are limited. The aim of the present study was to determine whether the presence of MG affects the prognosis of patients with thymoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 32 publications
2
33
1
5
Order By: Relevance
“…The prognostic value of MG associated thymoma remains controversial in the different reports of the literature, some established the presence of MG as a good survival prognostic factor related to the onset of MG symptoms that leads a prompt approach and treatment (23)(24)(25); others reported that having MG or not, didn't show any statistical significance, same as our results (11,(26)(27)(28); and finally, some studies reported even a worse prognosis in patients with MG (17,29). This discrepancies are probably due to the wide range of clinical and pathogenic variants in MG patients, the present study has several limitations: the information was retrospectively acquired at a single institution, it includes only 64 patients and a referral bias should be considered, nevertheless, this report is valuable because in the best of our knowledge there is scarce information about MG and thymoma from Hispanic referral cancer centers; a study from 1991 had one of the largest population with MG and thymoma, and they reported a better overall survival in patients with MG compared with TnMG group (30).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The prognostic value of MG associated thymoma remains controversial in the different reports of the literature, some established the presence of MG as a good survival prognostic factor related to the onset of MG symptoms that leads a prompt approach and treatment (23)(24)(25); others reported that having MG or not, didn't show any statistical significance, same as our results (11,(26)(27)(28); and finally, some studies reported even a worse prognosis in patients with MG (17,29). This discrepancies are probably due to the wide range of clinical and pathogenic variants in MG patients, the present study has several limitations: the information was retrospectively acquired at a single institution, it includes only 64 patients and a referral bias should be considered, nevertheless, this report is valuable because in the best of our knowledge there is scarce information about MG and thymoma from Hispanic referral cancer centers; a study from 1991 had one of the largest population with MG and thymoma, and they reported a better overall survival in patients with MG compared with TnMG group (30).…”
Section: Discussionsupporting
confidence: 73%
“…Thymectomy is the cornerstone treatment modality in patients with early stages of TET and is an approved treatment modality for patients with seropositive MG even without thymoma (15). Thymectomy in patients with T has a probability of complete remission of 28-48% (16), a complication rate of 20% (blood vessel damage, postoperative myasthenic crisis, pain, and infection) and a 2% mortality (17).…”
Section: Original Articlementioning
confidence: 99%
“…The existence of MG complicates the treatment of thymoma and may have a negative effect on prognosis. Previous studies have indicated that MG is an indicator of poor prognosis for thymomas . Worsened myasthenic symptoms or crisis may delay postoperative adjuvant treatment, reduce tolerance to radiotherapy or chemotherapy, and increase perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the prognosis of patients with MG with thymoma. In some studies, it has been indicated that the presence of thymoma adversely affected prognosis, but other authors have stated that patients with thymic carcinoma in association with MG had a better prognosis [21,22]. Some researchers have also concluded that thymoma did not cause any significant change in an MG prognosis [23].…”
Section: Discussionmentioning
confidence: 99%